Utilization of Pomegranate Peel Pectin as a Functional Ingredient for Nutritive Jelly Formulation: A Step Toward Healthier Processed Food - Roy, Trishna; Yeasmin, Nilufa; Begum, Ayesha; Hossain, Md. Altaf; Haque, Mohammad Mozibul; Nishan, Kanij Fatema; Mamun, Md. Zia Uddin Al; Mahfuza, Anjum; Pomy, Sultana Jannat (Knowledge Dynamics, 2025)
Background: The growing prevalence of chronic diseases has increased interest in natural functional foods over synthetic alternative. Pomegranate peel pectin, a natural gelling agent with dietary fiber, bioactive substances that helps with better digestion, glycemic control and antioxidant defense. As a healthy substitute for commercial pectin, the current study aimed to extract pectin from pomegranate peel and assess its stability and functionality in jelly preparation. Methods: Pectin was extracted from pomegranate peel powder using citric acid. Fourier Transform Infrared (FT-IR) spectroscopy was used to investigate structural characteristics. Galacturonic acid, amidation, ash content, degree of methyl esterification, and water holding capacity of the extracted pectin were all measured. Pomegranate juice’s proximate composition was ascertained. Both commercial and extracted pectin were used to make the jellies, sweetened with sugar or honey and tested for proximate composition, fiber content, antioxidant activity, sensory quality, and microbiological safety while being stored. Results: The extracted pectin yield was 8.2%, with a high methoxyl content, 1.15% ash, and 235.25% water-holding capacity. Pomegranate juice contained 85.3% moisture, 10.5%, total sugars, 0.15g citric acid, 0.9g ascorbic acid, and 0.03g ash. Jellies made with extracted pectin showed similar sensory and proximate property to those made with commercial pectin. Fiber content increased in jellies with extracted pectin, particularly with honey. Microbial investigation found sugar-added jelly safe for two months and honey-added for three months when refrigerated. Conclusion: This study shows pomegranate peel pectin, a health promoting organic substitute for commercial pectin, can be effectively used in jelly formulation.